Quantum Size Effects and Transport Phenomena in PbSe Quantum Wells and PbSe/EuS Superlattices - Rogacheva, E. I.; Nashchekina, O. N.; Olkhovskaya, S. I.; Sipatov, A. Yu.; Dresselhaus, M. S. (AIP Publishing LLC, 2013)
It is established that the room-temperature dependences of transport properties on the total thickness of PbSe layers d in PbSe/EuS superlattices exhibit an oscillatory behavior. It is shown that the oscillation period Δd practically coincides with the period of the thickness oscillations observed earlier in single PbSe/EuS quantum well. The non-monotonic character of these dependences is attributed to quantum size effects. The theoretically estimated and experimentally determined Δd values are in good agreement.
Keywords: PbSe; quantum well; superlattice; transport phenomena; quantum size effects